Volume for Winners and Losers: Taxation and Other Motives for Stock Trading - LAKONISHOK, JOSEF; SMIDT, SEYMOUR (Journal of Finance, 1986)
ABSTRACT Capital gains taxes create incentives to trade. Our major finding is that turnover is higher for winners (stocks, the prices of which have increased) than for losers, which is not consistent with the tax prediction. However, the turnover in December and January is evidence of tax‐motivated trading; there is a relatively high turnover for losers in December and for winners in January. We conclude that taxes influence turnover, but other motives for trading are more important. We were unable to find evidence that changing the length of the holding period required to qualify for long‐term capital gains treatment affected turnover.